Faith and Reason: A Catholic Perspective on Epistemology - I Gede Januarsa; Setyaningrum susanti; Risa Musyayyada (International Forum of Researchers and Lecturers, 2024)
This paper explores the interplay between faith and reason within the Catholic intellectual tradition. It revisits foundational works of Thomas Aquinas and Augustine to provide a framework for understanding knowledge acquisition through divine revelation and rational inquiry. The article also addresses contemporary challenges in integrating faith with scientific advancements and secular ideologies.